The physiologic sclerotic dentin: A literature-based hypothesis. Issue 6 (December 2015) - Kabartai, F.; Hoffmann, T.; Hannig, C.
Abstract: Despite the many hypotheses trying to explain how the physiologic sclerotic dentin is formed, there has been so far no convincing explanation for all of its observations. In this review, we tried to make a hypothesis based on the facts published to date. We found that the apoptosis of odontoblasts, which takes place after the formation of the apical constriction, may be the key-factor for the development of physiologic sclerotic dentin, because the resulting apoptotic bodies cannot be eliminated through phagocytosis and become trapped within the dentinal tubules due to the continuous formation of secondary dentin. The apoptotic bodies suffer later from a secondary or apoptotic necrosis leading to the release of the internal contents of pyrophosphate and hydrogen phosphate. Pyrophosphate can dehydrate the dentin and hydrogen phosphate can demineralize it, leading to the release of Ca 2+ ions which then contribute to the intratubular mineralization.